2014
DOI: 10.1002/ptr.5250
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Effects of Kamikihito in Japan and Kami-Guibi-Tang in Korea on Memory Enhancement: Working Towards the Development of a Global Study

Abstract: Traditional medicine is widely used in East Asia, and studies that demonstrate its usefulness have recently become more common. However, formulation-based studies are not globally understood because these studies are country-specific. There are many types of formulations that have been introduced to Japan and Korea from China. Establishing whether a same-origin formulation has equivalent effects in other countries is important for the development of studies that span multiple countries. The present study compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Moreover, it has also been used for amnesia in prescriptions. [13][14][15] Recent studies have revealed that the ethanol extract of EZJ and its constituents produce hypnotic effects through the modulation of neurotransmitter systems including serotonergic and γ-aminobutyric acid (GABA)ergic systems. [16][17][18][19][20] Further, numerous brain pathology models have indicated memory-enhancing effects of EZJ.…”
mentioning
confidence: 99%
“…Moreover, it has also been used for amnesia in prescriptions. [13][14][15] Recent studies have revealed that the ethanol extract of EZJ and its constituents produce hypnotic effects through the modulation of neurotransmitter systems including serotonergic and γ-aminobutyric acid (GABA)ergic systems. [16][17][18][19][20] Further, numerous brain pathology models have indicated memory-enhancing effects of EZJ.…”
mentioning
confidence: 99%
“…Several studies have reported that KKT improves brain function and action in the central nervous system. KKT influences memory enhancement ( Watari et al, 2015 ) and ameliorates the impairment of spatial memory. Moreover, the possibility of using KKT to treat memory deficits has been suggested ( Egashira et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is described in Xue‐shi yi‐an , a medical book written in China in the 16th century. KKT has long been used in Japan for palpitations, amnesia, insomnia, loss of appetite, and depression . The indications for KKT in kampo medicine are the dual deficiency of qi and blood and a slight qi counterflow.…”
Section: Discussionmentioning
confidence: 99%
“…Kamikihito ( Jia‐Wei‐Gui‐Pi‐Tang ; KKT) is a kampo extract formulation containing 14 crude drugs: Ginseng Radix, Atractyloides Rhizoma, Poria, Bupleuri Radix, Zizyphi Semen, Longan Arillus, Astragali Radix, Angelicae Radix, Gardeniae Fructus, Polygalae Radix, Zizyphi Fructus, Glycyrrhizae Radix, Sanssureae Radix, and Zingiberis Rhizoma. KKT is known for its effectiveness in treating insomnia, loss of appetite, and depression . It is also widely used for the management of blood disorders and is effective against idiopathic thrombocytopenic purpura and bone marrow suppression by chemotherapy .…”
Section: Introductionmentioning
confidence: 99%